The Importance of Modern Technologies in Teaching Speaking to Language Learners - G’iyasov Rahmatillo; Mamadjanova Shohida (Central Asian Journal of Literature, Philosophy and Culture, 2022)
Speaking is considered one of the most important skills in learning a language. Speaking is a necessary tool for communication. In the classroom, enhancing the speaking skills of students has been an issue. In the fast developing 21st century various innovative technologies are being implemented to teach verbal skill in the classrooms. Technology is the way to get access with this our contemporary world.More than the process of communication, trade and transactions, today technology is widely used in educational sectors. Technological tools have been regarded as ways of helping students enhance language skills such as speaking skill. Internet, podcasts, video conferencing, videos and speech recognition software are considered the best tools for teaching speaking skill. This article is dedicated to the investigation of effective and innovative methods of speaking activities, usage of technologies in developing speaking skills.